Surgical treatment of recurrent subvalvular discrete membrane and left ventricular outflow tract stenosis in an adult patient with a history of congenital cardiac surgery. Issue 3 (31st January 2023) - Kahraman, Nail; Topal, Dursun; Coşkun, Gültekin; Tiryakioğlu, Selma Kenar; Topal, Serra; Altunal, Ayşe Merve; Binicier, Nöfel Ahmet; Demir, Deniz
Abstract: Left ventricular outflow stenosis can develop at the supravalvular, valvular, and subvalvular levels. Resection of strictures at the diffuse subvalvular level is very difficult. In such pathologies, Konno‐Rastan procedure provides very successful solutions as an anterior aortoventriculoplasty method. In this article, we performed anterior aortaventriculoplasty surgical treatment for tunnel type left ventricular outflow tract stenosis, recurrent subvalvular discrete membrane, and aortic regurgitation in an adult patient with a history of partial atrioventricular septal defect repair and subvalvular discrete membrane resection operation in early childhood. The Konno‐Rastan procedure, which we applied to the redo case, which is rarely used in adult patients and rarely seen in the literature, is shared.